Can the National Specially Monitored Firms program improve corporate environmental performance?—Empirical evidence from China - Zhong, Tingyong; Xu, Chaoya; Liu, Hui; Li, Jiangna (Frontiers in Environmental Science, 2023)
As an important measure of the reform of central environmental supervision, the National Specially Monitored Firms program has a significant impact on enterprise pollution control. However, there are few studies systematically studying the mechanism of this system on enterprise environmental performance. Based on the quasi natural experiment of the National Specially Monitored Firms program, this paper investigates the impact of central environmental supervision on corporate environmental performance by using the emission data of industrial enterprises from 2001 to 2009. It is found that the National Specially Monitored Firms program significantly improved the corporate environmental performance of the monitored enterprises. Heterogeneity analysis finds that compared with enterprises with a higher degree of financing constraints, export enterprises and enterprises with a lower level of economic development in the region, the implementation of the National Specially Monitored Firms program has a more significant effect on improving the environmental performance of enterprises with a lower degree of financing constraints, domestic enterprises and enterprises with a higher level of economic development in the region. The mechanism test shows that improving enterprise environmental protection equipment investment is not the only intermediary mechanism for the National Specially Monitored Firms program to improve corporate environmental performance. The conclusions of this paper are not only conducive to optimizing environmental governance methods but also provide some inspiration for monitoring practices in other fields.